Does inhabitant’s fertility intention respond to housing status in the urban built environment: evidence from China - Zhuang, Xuefang; Li, Qingyin; Su, Tian; Zhang, Siying; Wu, Rong; Zheng, Tianxiang (Frontiers in Public Health, 2025)
The total fertility rate in China has been dropping in recent years, and this continuing trend has led to a series of problems. China has experienced periods of urbanization and housing reforms, leading to a significant boom in the real estate market. Housing status appears to be an essential factor influencing the fertility-related decisions of residents in China.We use cross-sectional data from a nationally representative large-scale tracking survey targeting the labor force in China. The research sample for this study comprised data from Chinese adults between the ages of 20 and 45. We highlight the importance of housing mortgages on fertility intention based on the Poisson regression model.Data was collected from a total of 7,512 inhabitants. The results show the following: 1) Housing status is closely related to fertility intention, while housing mortgage and water contamination are negatively affected. 2) The urban built environment, social environment, and individual characteristics affecting fertility intention mainly occur in urbanization rate, net primary productivity (NPP), life satisfaction, mental health, age, gender, marital status, political status, and education status. Urbanization rate, NPP, life satisfaction, mental health, and education positively influence resident's fertility intention, whereas women and single show lower fertility intention. 3) In particular, there are significant regional differences in the mechanism of fertility intention. Such intention in the eastern region are primarily related to housing mortgages, subjective well-being, life satisfaction, and the degree of water contamination in the habitat. Fertility intention in the central region are strongly related to social environment facts and population density, while those in the northeastern region are related to soil contamination and mental health. Conclusion: These results will contribute to the knowledge of the gradual decrease in fertility intention and provide multiple insights to make reasonable housing welfare and community micro-regeneration policies realize the future increase.